Optimization of baseline parameters and numerical simulation for Cu(In, Ga)Se2 solar cell - Za'Abar F.; Zuhdi A.W.M.; Bahrudin M.S.; Abdullah S.F.; Harif M.N.; Hasani A.H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Computer simulation; Computer software; Conversion efficiency; Electric network analysis; Electron affinity; Electronic properties; Energy gap; Heterojunctions; Numerical models; Open circuit voltage; Semiconductor doping; ATLAS software; Baseline data; CIGS solar cells; Electrical characterization; Heterojunction cells; Optical and electronic properties; Parameters optimization; Performance analysis; Solar cells